PSYCHOLOGICAL WELL-BEING AMONG ADOLESCENTS IN RELATION TO ACADEMIC SELF-CONCEPT AND THEIR FAMILY STRUCTURE (International Journal of Food and Nutritional Sciences, 2022)
Human development is characterized by several distinct and unique stages beginning with conception and ending at death. Like all stages of human growth and development, adolescence is an important stage. The present study comes under the domain of descriptive research. A sample of 200 students (100 girls and 100 boys) of IXth grade randomly selected from govt. and private schools were taken for study. Psychological well-being test by Sisodia and Choudhary (2005) and self-concept test by Saraswat (1971) as research tools were used to collect the data. Two-way ANOVA, t-test was used to analyses the data. Results showed that Self-concept of adolescent students belonging to nuclear family and joint family were not found different. Secondary school students differ significantly on Psychological well-being across gender. Psychological Well-being of male is higher than female students and adolescent students belonging to nuclear family and joint family were not found different.